SYSTEM AND FUNCTIONS OF POLITICAL COMMUNICATION ELEMENTS (Comparative Analysis of the Republic of Uzbekistan and the Russian Federation) (American Journal of Interdisciplinary Research and Development, 2022)
This article analyzed treatment of political communication as a function of the political system, as a functional element of the political system of the society ensuring the correlation between its other components. In addition, we were considered political communication elements of the Republic of Uzbekistan and the Russian Federation .